Undervisningsbegreppet och dess innebörder uttryckta av förskolans lärare - Jonsson, Agneta; Williams, Pia; Pramling Samuelsson, Ingrid (Forskning om undervisning och lärande, 2017)
I denna studie analyseras hur förskolans personal resonerar om att undervisa de yngsta barnen i förskolan. Fokusgruppssamtal har använts för att samla data från personal som arbetar med de yngsta barnens verksamhet. Billigs diskursteoretiska termer används i analyser av personalens resonemang om undervisningsbegreppets innebörder. Resultaten pekar mot två diskurser där krav och rättigheter utgör spänningsfält och där ett argument för något kan utgöra motargument i samma diskussion. Undervisning med de yngsta barnen utgör en del av en förskola i förändring. Med det i åtanke förstår vi personalens argument som motsägelsefulla när begreppet undervisning i förskolan beskrivs, något som kan ses både inom en diskurs och mellan diskurser. Teaching and its meanings expressed by preschool teachers The aim of this study is to analyse the preschool staff’s reflections on teaching the youngest children in preschool. Conversations in focus groups with preschool staff have been used for data collection. Theoretically the study considers Billigs concept concerning argumentation that has influence on discourses in change. The concept is used to view that an utterance about something that belongs to a particular discussion, stating that teaching can be understood as an explicit or implicit contradiction to the same discussion. The results point out two discourses where the demands and rights are seen as fields of tensions where an argument for something can, at the same time constitute arguments against something. Teaching the youngest children is part of a preschool in change. With that in mind, we understand the arguments as contradictory when the concept of teaching in preschool is described by the staff, something which can be seen both within and between discourses.